Incidence of Snake bites in Dhanusha District of Nepal: a study in tertiary care centre - Mandal, RN; Ahmed, Z; Mishra, A; Das, RC (Janaki Medical College Journal of Medical Science, 2016)
Background and Objectives: Envenomation by poisonous snakes is considered as an occupational hazard. Snake bite is a common medical emergency and one of the important causes of mortality and morbidity in tropical region. Material and Methods: The present study was conducted in the emergency department of JMCTH. All the patients admitted to JMCTH from April 2014 to November 2014 with snake bite were followed up from the time of admission to throughout their stay in hospital. The data was obtained from hospital case records, direct interrogation from relatives, friends, person accompanying the patients. The information was collected in a pre-formed Proforma. Data were entered and analyzed using Microsoft Excel. Results: The victims of snake bite predominantly were male. Maximum numbers of snake bite cases were between the age group of 31 to 40 yrs and of low socio-economic status. 67.34 % cases were from rural areas and farmers were the most common victim (69.38 %). Conclusion: Maximum cases occurred during the summer and pre-monsoon months, during daytime and involved the lower limbs. Ptosis was the chief neurotoxic feature followed by dysarthria. Janaki Medical College Journal of Medical Sciences (2015) Vol. 3 (1):52-55